Strategic Governance of Business Platforms: From Autocracy To Open Source Control Systems - Filatotchev, Igor; Santaló, Juan (My University, 2024)
This perspective article focuses on business platforms as new forms of organization and governance within the decision-making centralization/decentralization continuum. It aims to address the following research questions: How does the context of business platform creates new theoretical challenges regarding the traditional centralization/decentralization of governance debate? What are the main cost-benefit trade-offs regarding (de) centralization of decision-making process in a platform’s organizational “ecosystem”? The paper outlines the platforms’ governance spectrum that ranges from a high degree of centralization to the “open source” governance model. This is followed by a discussion of drivers of governance models including an interface between platform-specific investment and heterogeneity of platform participants. The paper concludes with an outline of implications for future research and practice.
Keywords: 53 Ciencias Económicas; ODS 8 - Trabajo decente y crecimiento económico; Platform governance; decentralization; platform performance